Japanese Perspectives on the Death of Christ : A Study in Contextualized Christology - Chuang, How (Book collections on Project MUSE., 2021)
Writing with an international theological background and his experience as a missionary in Japan, How Chuang Chua presents an extremely insightful study in contextualized Christology. The careful expositions of the writings of Kitamori, Endo, and Koyama are a feast of insights into Japanese culture and theology. This book, however, is far more than an exposition of their thought. Dr. Chua also evaluates their writings for biblical fidelity and compares them to classical theories of the atonement. Their thoughts are also probed for their missiological relevance. This book brims with cultural a